Complex 'everyday' lives meet multiple networks: the social and educational lives of young children in foster care and their foster carers. (March 2020) - Meetoo, Veena; Cameron, Claire; Clark, Alison; Jackson, Sonia
The everyday lives of young fostered children are rarely studied. Using an ethnographic approach including interviews, walks, observation and photomap making, this article reports on the findings from a unique pilot study of the social and educational lives of young foster children (aged 0‒4) in an inner London borough. The following findings are presented: (1) what foster carers do: everyday lives and education; (2) foster carers' meanings and perspectives on early education; and (3) foster carers as 'everyday experts' in meeting complex needs. The findings demonstrate how foster carers fulfil multifaceted roles as they navigate complex everyday life with their young children. Ways in which foster carers may provide a 'stimulating' environment and the barriers and difficulties they encounter are discussed.